THE DISTRIBUTION OF Fe, Al, Cu, Co, Cr, Ni, Zn IN ALFISOLS DEVELOPED ON GABBROS FROM KlLKIS AREA - Τσαουσίδου Π.; Τσαγκαλίδης Α.; Γκάρτζος Ε.; Χαϊντούτη Κ.; Γασπαράτος Δ.; Ταρενίδης Δ. (Bulletin of the Geological Society of Greece, 2004)
The distribution of Fe, Al, Cu, Co, Cr, Ni, Zn was examined in two soil profiles of cultivated Alfisols developed from gabbro in the area of Chamilo in Kilkis. The main features of the studied soils were the accumulation of clay in the argilic horizons, the low pH and organic matter content, the absence of CaC03, and the high sand content, with differences in the drainage class and the degree of development. The optical microscope observations have demonstrated the presence of residual pyroxenes, altered plagioclases and muscovite. X-ray diffraction data of the clay fraction show the same clay minerals for the two soil profiles with the presence of kaolinite, illite, vermiculite and interstratified minerals of montmorillonite-vermiculite. The distribution of elements for both soil profiles depends primary from the pedogenetic processes. The illuvial translocation of clay in the argilic horizon seems to play an important role in the behavior of these elements in the studied soils. The significant correlations between the clay fraction, the Fe - Al oxides and the studied elements support the previous hypothesis. The use of ratio of elements concentration between the A and C horizons (index to assess the relative mobility of elements in the soil profile) which have values < 0.90 confirms the influence of the clay fraction at the distribution of elements. The low pH, the particle size distribution, and the drainage class of the soils influence also the dynamics of the studied elements in the soil profiles while the organic matter content seems to have no effect.